Pengembangan Keilmuan Program Studi Manajemen Pendidikan Islam Tinjauan Futurologi Pendidikan dan Pengembangan Kurikulum - Muhammad Amin; Sugiatno Sugiatno; Irwan Fathurrochman (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The background of this qualitative research is to look at the Curriculum IAIN as an Islamic Higher Education should have thought about the direction of the development of science in the future, if not then the Curriculum IAIN will be abandoned by both interested people and users, the results of the study indicate that the direction of scientific development of the MPI Study Program Department of Tarbiyah IAIN Curup refers to systemic theo-antrocosmocentric philosophy. The systemic theo-antrocosmocentric paradigm is the work of knowledge which is based on the efforts to attribute, enhance, and accommodate Islamic sciences, social-cultural sciences and science. Making these three families as a chain that cannot be broken which means to combine various elements of knowledge that originate from God and humanity. Deity consists of Islamic sciences including Islamic management. Humanity consists of sociology, culture, communication and science that develops and grows on local wisdom.